Testing local cocoa selections in Sulawesi: (ii) resistance to stem canker and pod rot (black pod) caused by Phytophthora palmivora. (November 2015) - Purwantara, Agus; McMahon, Peter; Susilo, Agung W.; Sukamto, Sri; Mulia, Sahardi; Nurlaila,; Saftar, Ashar; Purung, Hussin bin; Lambert, Smilja; Keane, Philip; Guest, David
Abstract: Cocoa genotypes, selected locally or obtained from the progeny of hybrid crosses and propagated clonally in two trials in Pinrang and Polman Districts, Sulawesi, were evaluated for resistance to Phytophthora pod rot (Ppr) and stem canker caused by Phytophthora palmivora . In each trial, 10–12 clones, including four common to both sites, were evaluated for infections occurring naturally on the farm or induced by artificial inoculation of stems and attached pods. At each site, incidence and severity of stem canker in the clones were evaluated in the early and late wet season of 2013/2014, while Ppr incidence was determined from the cumulative pod harvest of 2010–2012. Incidence and severity of stem canker in the six-year old trees were highly correlated in both years and were higher in Pinrang than Polman, with marked increases during the wet season occurring in more susceptible genotypes (e.g. 65.6%–90.6% incidence in GeniJ in Pinrang). Although Ppr incidence in all clones increased during wet periods, some clones maintained a lower incidence than others during the two year period of evaluation: for example, between the dry season of 2011 and following wet season average Ppr incidence increased from <5% to 26% in the local clone M06 and <20%–46% in the more susceptible RB. Average lesion size following artificial inoculation was higher in both pods and stems in the Pinrang, than the Polman, trial. Positive correlation between results of artificial pod tests and total field Ppr incidence (including immature and ripe pods) suggest that artificial inoculation of attached pods is a reliable method to evaluate Ppr resistance. Similarly, lesion size in different clones following artificial inoculation of stems was positively correlated with naturally occurring stem canker severity. Inconsistencies between responses to inoculated and naturally occurring P . palmivora were found in some clones, for example, ICCRI04, selected from progeny of a hybrid cross with Sca12, and Geni J, a local farm selection, indicating the importance of confirming artificial resistance tests with evaluations on the farm. While resistance to both diseases was confirmed in some local selections notably M06, M05 and Panimbu Red, no significant correlation occurred in either trial in the responses to stem canker and Ppr (whether naturally occurring or induced artificially by inoculation), suggesting independent resistance mechanisms may operate in stems and pods. Broad-sense heritability estimates, based on clones common to the two trials, were high (0.85 and 0.63 for stem canker incidence and severity, respectively, and 0.41 for Ppr incidence) indicating a strong influence of host genotype on the response to P . palmivora . Highlights: Cocoa farm selections and hybrid progeny were evaluated for Phytophthora pod rot (Ppr) and stem canker in trials in Sulawesi. A low incidence of Ppr or canker was maintained during the dry and wet seasons in some clones indicating resistance. Lesion development following artificial inoculation was positively correlated with disease in the field. Lesion size in pods and stems following artificial inoculation was not correlated. Broad sense heritability estimates for resistance were high, particularly in stems.